BRAKING MODE IMPROVEMENT IN INDUCTION MOTOR DRIVE DUE TO THE TORQUE MAXIMIZATION WITH FIELD WEAKENING - Pryimak, B. I. (Visnyk of Vinnytsia Politechnical Institute, 2016)
The work is dedicated to improving the performance of vector-controlled high-speed induction motor drives. There have been studied the boundary characteristics of the induction motor with maximization of torque at field weakening in generator mode. Simulation of extreme induction motor control system has confirmed a significant reduction of the motor braking time at high speeds.